Improving Learning of Programming Through E-Learning by Using Asynchronous Virtual Pair Programming - Abdullah Mohd Zin,; Sufian Idris,; Nantha Kumar Subramaniam, (2006)
The problem of learning programming subjects, especially through distance learning and E-Learning, has been widely reported in literatures. Many attempts have been made to solve these problems. This has led to many new approaches in the techniques of learning of programming. One of the approaches that have been proposed is the use of virtual pair programming (VPP). Most of the studies about VPP in distance learning or e-learning environment focus on the use of the synchronous mode of collaboration between learners. Not much research have been done about asynchronous VPP. This paper describes how we have implemented VPP and a research that has been carried out to study the effectiveness of asynchronous VPP for learning of programming. In particular, this research study the effectiveness of asynchronous VPP in the learning of object-oriented programming among students at Open University Malaysia (OUM). The result of the research has shown that most of the learners have given positive feedback, indicating that they are happy with the use of asynchronous VPP. At the same time, learners did recommend some extra features that could be added in making asynchronous VPP more enjoyable. (Authors' abstract)